International perspective for a sound intergovernmental finance system in the Philippines. (2012)
This paper describes briefly the different forms of equalization, principally focusing on the distinction between revenue equalization versus cost equalization. In addition, some international country case studies from Australia, Canada, Germany, and Switzerland are presented. Based on these country cases, suggestions are made as to how the Philippines can avoid pitfalls in the area of fiscal federalism and what lessons it can learn from other countries for the next 20 years. This will enable readers to decide how common or unique the Philippine experience is, and what achievements and failures can be observed in the Philippines in comparison with other developing countries.
Keywords: Decentralization in government; Internal revenue; Revenue sharing; Intergovernmental fiscal relations